Polar auxin transport - Baluska, František; Chen, Rujin (Signaling and Communication in Plants, 2013)
The importance of the plant growth regulator auxin for plant growth has long been recognized, even before the discovery of its chemical structures in the early 20th century. Physiological studies in the decades since have demonstrated that auxin is unidirectionally transported in plants, a process dubbed polar auxin transport. It is the polar auxin transport process that generates a local auxin concentration gradient and regulates a broad array of physiological and developmental processes. The discoveries of auxin transport carrier proteins that mediate auxin influx into and efflux out of transport-competent cells and auxin receptor proteins for auxin signaling in the last few decades represent significant milestones in auxin research and open up opportunities to probe the cellular and molecular processes that regulate auxin transport and integrate environmental cues with signaling processes. Remarkably, components of the polar auxin transport machinery are present in both lower plants such as mosses and higher plants including monocots and eudicots, illustrating the key role of polar auxin transport in plant evolution.  This book highlights topics ranging from physiological and genetic studies of polar auxin transport in plant development, to growth responses to the environment and plant-microbe interactions, to hormonal cross-talks with various cellular and molecular regulatory processes essential for polar auxin transport.